Tourist satisfaction dimension in Kinabalu park, Sabah, Malaysia - Timothy Ajeng Mereng; Hamimah Talib; Chan, Jennifer Kim Lian (Universiti Malaysia Sabah, 2020)
This paper aims to identify the tourist satisfaction dimensions in Kinabalu Park as a World Heritage Site, to come out with the tourist satisfaction indicators for responsible rural tourism framework at Kinabalu Park, Sabah, Malaysia, in terms of satisfaction and dissatisfaction dimension. One of the data sources to achieve this aim is the in-depth interview session with the tourist in Kinabalu Park, specifically the mountain climbers. The interview was conducted with Herzberg’s Critical Incident Technique (CIT), which is a method that asks the respondents to recall their exceptionally good feeling as well as their exceptionally bad feeling during their experience in Kinabalu Park. The data were analyzed thematically based on Driver’s Recreation Experience Preference (REP) scale to identify the tourists’ satisfaction dimension. Our study found that “scenery enjoyment” was the most prevalent domain for a satisfying experience or the source of good feeling. Along with the “scenery enjoyment”, there were other three emerging experience domains that could contribute to understanding the tourist satisfaction dimensions in Kinabalu Park